Reviews and notices - Alvar Ellegård; Sabina Kielow; Arne Olofsson; Ronald Paul; Ted Tapper; Magnus Ankarsjö; Monica Armini; Christine Pankow; Ingmar Söhrman; Gösta Björn; Frank-Michael Kirsch (Moderna Språk)
Includes the following reviews: